Peningkatan Pemahaman Pengaplikasian M-Pajak berbasis Android dan iOS kepada Wajib Pajak bersama Relawan Pajak IBI Kosgoro 1957 Masa Bakti 2024 di Kecamatan Ciampea, Bogor Barat - Rahmadi, Zara Tania; Yulianto, Kampono Imam; Dharma, Dias Adi; Putra, Febryano Manggala; Wahyudi, Muhammad Aria; Pemadi, Syifa Febyca Nur; Rayan, Rayan; Susetyawan, Angellina Merry (ASOSIASI IDEBAHASA KEPRI, 2025)
Community devotionals in Ciampea, west bogor, aim to increase the understanding and application of android based m-tax applications and ios among taxpayers. On Saturday, April 27, 2024, with the participation of 20 taxpayers. Socialization includes the introduction of applications features such as billing code, billing profile Settings, and the location of nearby tax services, while fellowmen provide tutorials to make accounts, generate billing codes, and make tax payments online. It is expected to increase the efficiency of tax reporting and active engagement of taxpayers in the tax process in Indonesia.